Pharmacokinetics and pharmacodynamics of the nucleoside sparing dual regimen containing rilpivirine plus darunavir/ritonavir in treatment-naïve HIV-1-infected individuals. Issue 1 (2nd January 2018) - Jackson, Akil; Else, Laura; Higgs, Christopher; Karolia, Zeenat; Khoo, Saye; Back, David; Devitt, Emma; Pozniak, Anton; Boffito, Marta
Abstract : Background: We aimed at investigating the antiviral activity and the pharmacokinetics of the dual antiretroviral (ARV) combination of rilpivirine plus darunavir/ritonavir 25/800/100 mg once-daily in naïve HIV-1-infected individuals (NHII) with different baseline viral loads. Settings: Pharmacokinetic/pharmacodynamics study in ARV-naïve HIV-infected individuals. Methods: The primary endpoint was the number of NHII with HIV-RNA < 40 copies/mL at week 48. Secondary endpoints included rilpivirine/darunavir/ritonavir pharmacokinetics, HIV-RNA decay, and changes in ECG QT interval. Results: Thirty-six individuals were enrolled, 18 with a baseline viral load < 100, 000 copies/mL (group A) and 18 with a baseline viral load > 100, 000 copies/mL (group B). All but 1 (HIV-RNA = 63 copies/mL) subjects achieved viral load < 50 copies/mL by week 36, and all at week 48. Median (range) HIV-RNA reduction (Log10 copies/mL) was 1.3 (0.6–1.9) over the first week, with no differences between groups A and B. Geometric mean and 95%CI rilpivirine C max, C trough, AUC were 183 (165–239), 114 (104–109) ng/mL, 2966 (2704–3820) ng h/mL. No QTcF interval changes were recorded. Conclusions: rilpivirine/darunavir/ritonavir could be efficacious, with limited short-term toxicity in ARV-naïve patients. Although rilpivirine was co-administered with ritonavir, its exposure was within ranges measured during phase III trials.